Cerebrovascular Disease Is a Risk for Getting Lost Behavior in Prodromal Dementia. Issue 5 (August 2019) - Yatawara, Chathuri; Ng, Kok Pin; Lim, Levinia; Chander, Russell; Zhou, Juan; Kandiah, Nagaendran
Cerebrovascular disease (CVD) contributes to spatial navigation deficits; however, the everyday outcomes of this association remain unexplored. We investigated whether CVD was a risk for getting lost behavior (GLB) in elderly with mild cognitive impairment (MCI) and mild Alzheimer disease (AD). Getting lost behavior was assessed using a semistructured clinical interview and was associated with white matter lesions (WMLs) in patients with MCI. Specifically, right occipital WMLs increased the odds of GLB by 12 times ( P = .03) and right temporal WMLs increased the odds of GLB by 4 times ( P = .01), regardless of age, gender, global cognitive impairment, and occipital or medial temporal gray matter atrophy. Hypertension increased the risk of GLB in MCI by contributing to the burden of WMLs. White matter lesions were not associated with GLB in mild AD. Our findings suggest that interventions aimed at reducing GLB in prodromal dementia may involve preventing WMLs by optimizing hypertension control.